THE ANALYSIS OF COOPERATIVE PRINCIPLE IN CORBUZIER PODCAST OF SITI FADILAH, SEBUAH KONSPIRASI – SAYA DIKORBANKAN EPISODE - Anggrarini, Natalia; Dian Rosdiana, Deuis (Gema Wiralodra, 2020)
Discussing the misleading of information in interaction in Podcast is rare in language research. Considering the concept of cooperative principle and the failure of observing maxims in an interaction by Grice (1989[1967]), this research investigated the flouting and violating of maxims appears within the podcast. The data source of study is a podcast of Deddy Corbuzier with Siti Fadilah Supari, the Former of Indonesian Health Minister which entitled Siti Fadilah, Sebuah Konspirasi – Saya dikorbankan. This study discovers the participant’s failing to observe the maxims, in form of flouting and violating. There are 57 exchanges flouted as the most common participant’s failure in observing the maxims, which consists of 29 quantity maxims (50%), 14 manner maxims (25%), 9 quality maxims (16%), and 5 relation maxims (9%). Then it is followed by the violation in 7 exchanges, which occurs in 3 quality maxims (43%), 2 quantity maxims (29%), 1 relation maxim (14%) and 1 manner maxim (14%). The study finds the podcast provides the various information, since the participant provides the more contribution rather than is required as the domination of flouting in quantity maxim. This study implies the need of reconfirming of the utterance that is presumable to lead failure of information understanding.